Comorbid Mental Illness and Poor Physical Function Among Newly Admitted Inmates in Connecticut's Jails. (April 2014) - Barry, Lisa C.; Ford, Julian D.; Trestman, Robert L.
The prevalence of co-occurring mental illness and poor physical functioning among inmates, and whether there are differences according to age or gender, is largely unknown. Of the 315 new inmate admissions into Connecticut's jails with a current psychiatric diagnosis, 97 (30.9%) had poor physical function. Compared with inmates aged 18 to 24, those aged 25 to 39 and those ≥ 40 had increasingly higher likelihoods of having poor physical function overall, and among men and women separately. Whereas women were more likely to report poor physical functioning than men overall and within age groups 18 to 24 and 25 to 39, the effect of gender was nonsignificant in the oldest age group. Future research should determine whether poor physical function is associated with worse health-related outcomes among inmates with mental illness.